Physiological and Blood Response in Goat Kids Disbudding by Subcutaneous Injection of Eugenol and Cautery - FarajliAbbasi, M; Molaei, MM; Sharifi, H; Oloumi, MM; Behzadi, A (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was aimed to compare the pain in five days old goat kids disbudding by eugenol and cautery method. the eugenol is known as a main factor in novel disbudding method named clove oil. In this study, serum cortisol levels, and clinical changes were evaluated to compare disbudding by eugenol and cautery. A total of 25 Raieni (Cashmere) goat kids aged 5 days old were randomly allocated to 1-5 treatment groups (n=5), To differentiate the pain caused by disbudding with the stress of restraint and blood sampling in the results, the animals in both methods of disbudding were divided into different groups according to the evaluated parameters; groups 1,2 cautery-disbudded(550°C,3-6s), and groups 3-5 SC eugenol(0.1cc) administration- disbudded. The cortisol serum level immediately after disbudding in group 2 was 7.94±0.02 µg/dL, vs. group 4, 6.34±0.03 (mean ± SE), and over time, the values were in favor of the eugenol group, despite being insignificant up to 240 and 480 minutes after defoliation. The respiratory rate in group 3 was 77±1.13 vs. group 1, 108±0.67 (mean ± SE), and pulse rate in group 3 was 239.4±1.13 vs. group 1, 284±1.53; and rectal temperature showed no significant difference among groups 1&3. In group 5, there was no significant difference between before and after cell blood count and blood enzymes analysis, which could be an argument for the lack of effect of eugenol on vital organs. The results showed less stress and pain level in eugenol-disbudded groups compared to cautery-disbudded in goat kids (P≤0.05). Analysis of specific blood serum enzymes represented no side effect on vital organs in eugenol injection. Our data suggest that eugenol may be a suitable alternative to old and outdated or painful routine disbudding methods. The difference in our findings with similar studies can be due to the difference in the methodology of sampling., analysis and measurement accuracy. However, more research with wide aspect on pain reliability, availability, economy, and behavioral is needed to assess whether eugenol can replace other methods.